Unfolding the Leaf: A Comprehensive Insight into Phyllodes Tumors of the Breast: A Review Article (Asian Journal of Pharmaceutics (AJP), 2025)
Phyllodes tumors (PTs) are uncommon fibroepithelial lesions of the breast that comprise